Binge Alcohol Intake After Hypergravity Stress Sustainably Decreases AMPK and Transcription Factors Necessary for Hepatocyte Survival. (30th November 2016) - Lee, Sang Gil; Wu, Hong Min; Lee, Chan Gyu; Oh, Choong Sik; Chung, So Won; Kim, Sang Geon
Abstract : Background: Binge alcohol consumption elicits mitochondrial dysfunction in hepatocytes. An understanding of the effect of ethanol (EtOH) exposure after hypergravity stress on liver function may assist in the implementation of pathophysiological countermeasures for aerospace missions. This study investigated whether a combination of hypergravity stress and binge alcohol intake has a detrimental effect on AMP‐activated protein kinase (AMPK) and other molecules necessary for hepatocyte survival. Methods: The mice were orally administered a single dose of EtOH (5 g/kg body weight, 20% EtOH) immediately after a load to +9 Gz hypergravity for 1 hour using a small animal centrifuge and sacrificed 24 hours after treatment. For the multiple‐dose model, 3 consecutive daily treatments were carried out. Immunoblottings were carried out on liver homogenates. Results: Binge alcohol intake in mice immediately after a 1‐hour exposure to a +9 Gz hypergravity load repressed hepatic Akt and PARP‐1 levels at 24 hours posttreatment. Moreover, it sustainably diminished the level of AMPKα, a key regulator of energy metabolism, as compared to each individual treatment. Similarly, the combination of alcohol and hypergravity suppressed the levels of STAT3, FOXO1/3, C/EBPβ, and CREB, transcription factors necessary for cell survival. Similar changes were not detected after 3 consecutive daily combinatorial treatments, indicating that repetitive training with hypergravity loads provides hepatoprotective effects in a binge alcohol model. Conclusions: These results show that binge alcohol exposure in mice immediately following a +9 Gz hypergravity stress persistently decreased AMPKα and other key molecules required for hepatocyte survival, and these changes may be reversed by repetitive hypergravity loads. Abstract : Binge alcohol consumption elicits mitochondrial dysfunction and apoptosis in hepatocytes. This study showed that a combination of hypergravity stress and binge alcohol intake has a detrimental effect on AMPK, a key regulator of energy metabolism, and other molecules necessary for hepatocyte survival. Binge alcohol intake after hypergravity stress diminished the levels of AMPK α, FOXO1/3, STAT3, and other transcription factors in the liver of mice compared to individual treatment, and these changes were prevented by repetitive hypergravity loads.